PENGARUH MODEL PEMBELAJARAN SOMATIC, AUDITORY, VISUAL, INTELLECTUAL TERHADAP KEMAMPUAN METAKOGNITIF DAN KECERDASAN EMOSIONAL PADA MATERI SISTEM EKSKRESI KELAS VIII DI MTsN - Aryani Dwi Kesumawardani; Fitri Nurmalasari; Heru Juabdin Sada; Raicha Oktafiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to determine the effect of the Somatic, Auditory, Visual, Intellectual learning model on the metacognitive ability and emotional intelligence of eighth-grade students at MTsN 1 Bandar Lampung. This study was driven by the low metacognitive ability and emotional intelligence observed among students, as indicated by pre-research scores. This condition was mainly influenced by conventional learning processes that lacked active student participation, thus necessitating a contextual innovation to enhance more active, meaningful, and sustainable engagement. The research method used was a quasi-experimental approach with a posttest-only control design. The research sample was obtained using cluster random sampling, involving two classes, namely class VIII A as the experimental class, which implemented the Somatic, Auditory, Visual, Intellectual learning model, and class VIII B as the control class, which applied the Discovery Learning model. The instruments used in this study consisted of essay questions to measure metacognitive ability and a questionnaire to assess emotional intelligence. The data analysis technique employed was the Independent Sample T-Test. Based on the hypothesis testing results, the Sig. (2-tailed) value obtained was 0.000 < 0.05, indicating that the implementation of the Somatic, Auditory, Visual, Intellectual learning model had a significant effect on improving students’ metacognitive ability and emotional intelligence at MTsN 1 Bandar Lampung. Therefore, the Somatic, Auditory, Visual, Intellectual learning model is effective in enhancing metacognitive ability and emotional intelligence.